MEMBANGUN KEPEMIMPINAN YANG BERAKAR PADA BUDAYA: STUDI PUSTAKA TENTANG NILAI-NILAI MINANGKABAU DALAM KONTEKS KEPEMIMPINAN KONTEMPORER - Herlina Saswita; Nurhayati; Novriandi; Hafizul; Irma Yendi; Alfroki Marta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore leadership development rooted in Minangkabau cultural values in a modern context. The issue raised is the challenges faced by the younger generation in maintaining cultural values amid the influence of globalization and social change. The methodology used was a qualitative approach with a literature study design, which involved analyzing literature related to transformational, situational, and participatory leadership theories, as well as the application of Minangkabau cultural values. The results showed that effective leadership can be achieved by integrating cultural values such as gotong royong and deliberation in leadership practices. In addition, leadership development strategies that include training, education, and the use of technology are needed to strengthen the involvement of the younger generation. Practical projects, such as youth leadership programs and cultural festivals, have proven effective in strengthening cultural values among the younger generation. Further research is needed to explore the long-term impact of these programs and identify best practices in different contexts.